Design para forças de caráter : estudo sobre a aplicação da abordagem de design voltada ao bem-estar subjetivo - Daudt, Francielle (Universidade do Vale do Rio dos Sinos, 2018)
Contributions in the area of Emotional Design, although important, are insufficient when it comes to long-lasting impacts on individuals. Therefore, new theoretical proposals, such as Positive Design, have been gaining strength, since they focus on the subjective well-being of users, generating long-lasting effects. Positive Design offers three important ingredients for stimulating that well-being: design for virtues, design for pleasure and design for personal significance. In this work, we intend to give focus on the stimulus of the virtues, which are manifested by character strengths. The character strengths are predispositions to feel and act, stemming from the virtues and moral values of individuals. To project from this perspective, there are five design elements that must be taken into account: be oriented to possibilities; balance between the three ingredients (personal significance, virtues and pleasures); personal fit; active user involvement and long-term impact. Knowing that Positive Design still not have consolidated design methods or techniques, it is proposed as a research problem: how designers use the Positive Design approach in projects focused on reinforcing individuals' character strengths? The investigations were carried out through an applied, exploratory research, in which the use of Positive design theory is experienced in design practices, based on the model of Tonetto et al. (2018). These practices were made with clients and designers, followed by focus groups with professionals. The methods of information collection were participant observation and focus group, and data analysis was done through content analysis. The main results were the difficulty of abstraction and generalization of the character strength proposed to a broader public, the influence of the characteristics of the client in different spheres of the project, design alternatives with social cultural impacts, difficulties in using the ingredient pleasure and facility in propose elements of personal adjustment. Finally, we suggest some lessons that may be pertinent to future projects and studies.
Keywords: Positive design; Design para o bem-estar subjetivo; Design para virtudes; Design para forças de caráter; Positive design; Design for subjective well-being; Design for virtue; Design for character strenghts; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial